Influencer Culture and Brand Communication: A Review of Emerging Trends and Ethical Concerns - Shushila Yadav; Nirmala Pandey (Journal of Advanced Research in Journalism & Mass Communication, 2025)
The rise of social media influencers has transformed brand communication, redefining credibility, engagement, and the meaning of authenticity. This review examines the development of influencer culture, identifies emerging trends such as micro-influencers, AI-driven creators, and value-based collaborations, and explores critical ethical challenges—transparency, authenticity, fake engagement, data privacy, and sustainability. Drawing from recent scholarly and industry sources, this article proposes a conceptual framework for ethical influencer–brand communication and offers recommendations for brands, influencers, and policymakers. The review concludes that sustainable success in influencer marketing depends on transparent practices, authentic storytelling, and ethical responsibility.